Finanzmarkt: Regulierung auf dem richtigen Weg? - Sebastian Dullien; Stephan Paul; Christian A. Conrad; Max Otte (Wirtschaftsdienst, 2012)
Fünf Jahre nach dem Ausbruch der Finanzmarktkrise hat sich einiges getan: Die USA und die Mitgliedstaaten der Europäischen Union haben verschiedene Regulierungen auf den Weg gebracht. Die Autoren beurteilen dies allerdings unterschiedlich. Zum einen seien die Regulierungen nicht ausreichend und nicht zielgenau, zum anderen sind Unklarheiten und eine Vermengung von Kompetenzen entstanden. Zudem stellt sich die Frage, ob eine striktere Finanzmarktregulierung den Kern des Problems trifft. – – Immediately after the financial market crisis of 2008/2009 many politicians and economists insisted on a stricter regulation of financial markets. Since then the governments in the USA and the EU have signifi cantly tightened financial market regulation and oversight. But there are conceptual and technical problems with the latest Basel III proposals as well as with the institutional design of banking supervison. Not only rules for banking operations, but also credit rating agencies, accounting standards and the organisational structure of banks should be considered on the way to sound fi nancial markets. However, the new legislation will not succeed in making the global financial system crisis-proof as a number of problems such as global imbalances, excessive complexity in the financial sector and inherent instability of asset prices have not been addressed. There is no consensus among the authors on the ability and willingness of politicians to achieve better regulated financial markets.
Keywords: E44; F34; G01; 330; Finanzmarktkrise; Kapitalmarktregulierung; Bankenpolitik; Wirkungsanalyse; Ordnungspolitik; USA; Europa